2010
DOI: 10.1103/physrevb.82.094107
|View full text |Cite
|
Sign up to set email alerts
|

Stability of simple cubic calcium at high pressure: A first-principles study

Abstract: The origin of the temperature dependence of the stability of the simple cubic ͑sc͒ structure of Ca in the pressure range 32-109 GPa is investigated by the use of plane-wave density-functional calculations and first-principles molecular-dynamics ͑MD͒ simulations based on localized basis set method employed in the SIESTA code. Constant-pressure MD simulations are performed on the competing sc and I4 1 / amd structures in this pressure range. The results are analyzed to recover details of the structures and dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…In brief, sX-LDA functional treats d electron differently compared to other functionals, 22,36,[42][43][44][45] PBE and LDA, see Fig. 4.…”
Section: Figmentioning
confidence: 99%
“…In brief, sX-LDA functional treats d electron differently compared to other functionals, 22,36,[42][43][44][45] PBE and LDA, see Fig. 4.…”
Section: Figmentioning
confidence: 99%
“…The formation energy of Li vacancy in the Li 12 Si 7 alloy E f (Vac Li ) was calculated using the equation (1): Ab initio molecular dynamics (MD) simulations were performed within the framework of DFT as implemented Spanish Initiative for Electronic with Thousands of Atoms (SIESTA) code [49][50][51][52] . All calculations were performed using the 152 atoms supercell with one Li vacancy.…”
Section: Computational Detailsmentioning
confidence: 99%
“…On the other hand, high-pressure room temperature experiments confirmed that Ca-III adopts the nearly sc structure (8). To overcome this discrepancy, Teweldeberhan et al (16) used diffusion quantum Monte Carlo calculations, Errea et al (18) used ab initio methods including anharmonic effects to stabilize the sc phase at room temperature, and Yao et al (17) provided a detailed analysis of ab initio molecular dynamics simulations that could account for the stability of the sc structure at room temperature. The remaining major discrepancy is that Yao et al (14) and Oganov et al (13) predicted that Ca with I4 1 ∕amd symmetry (β-tin structure) has a much lower zero-temperature enthalpy than sc, but in spite of many experimental efforts, the presumably more stable β-tin structured Ca has never been discovered.…”
mentioning
confidence: 99%
“…The pressure-induced electronic transition from a normal metal to a superconductor occurs in the Ca-III phase region above 44 GPa (10,11), and the T c increases with pressure from 2 K to 10 K within the Ca-III region (6). Ca-III is also a very active test case of modern theories and experiments, where a number of paradoxes arise (12)(13)(14)(15)(16)(17)(18). Based on density-functional theory (DFT) calculations, Ca-III with sc structure has imaginary phonon frequencies, indicating dynamic instability (19)(20)(21).…”
mentioning
confidence: 99%